Konflik dengan pasangan, tujuan berprestasi, dan hubungannya dengan self-regulated learning pada pelajar berusia remaja - Putri Saraswati (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2021)
Teens begin to be attracted to the opposite sex, some even have romantic relationships with the opposite sex. In relation to other people, it is very possible to cause conflict. Differences experienced by two people (pairs) can cause interference in learning, especially if the person does not have a clear achievement goal in learning. This study aims to determine the relationship between the ability of adolescents in overcoming conflicts with partners, achieving goals, and independent learning. The subjects of this study were 388 high school students, 182 male students and 206 female students. The sampling used is cluster random sampling. The data was taken in the city of Malang and the Likert scale is a measuring tool used for the third variable. The results of this study indicate that 1) there is no relationship between romantic partner conflict and SRL (r=0.48, sig=0.344<0.05); 2) however, achievement goal is not a mediating for romantic partner conflict variable and SRL; 3) there is a positive relationship between romantic partner conflict and the achievement goal (r = 0.122, sig = 0.016).